Group Tutoring Services Using Short Film Media Methods to Improve Student Discipline at SMK PGRI 2 Giri: Penerapan Layanan Bimbingan kelompok Dengan Metode Media Film Pendek Untuk Meningkatkan Disiplin Siswa SMK PGRI 2 Giri - Wanda Ayu Aprilin; Heriberthus Wicaksono; Ratna Wulandari (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
This study aims to determine the application of group guidance services with short film media methods can improve student discipline at SMK PGRI 2 Giri Banyuwangi. This type of research is True Experimental research with Pre-test Post-test Control Group Design conducted at SMK PGRI 2 Giri. The population of this study was all class X which amounted to 185 students. The sample selection is by random sampling. The sample selection obtained 2 classes, namely the experimental class X TBSM 2 while the control class X TITL. The data collection technique was carried out using a Likert Scale model questionnaire with five answer options. The data obtained were analyzed using the T-test. The results showed differences in student learning discipline with an average value in the experimental class pre-test results of 95 and post-test of 154. While the average control class pre-test was 94 and post-test was 152. With df = 48 at a significant level In the output results of the Independent Sample T-test test, the tcount value is 2.918 while the ttable value is 1.677, meaning that tcount> ttable 2.918> 1.677. When analyzed from the basis of decision making or acceptance criteria, H0 is rejected and Ha is accepted, which reads “Group Guidance Services with Film Media Methods to Improve Student Discipline at SMK PGRI 2 Giri”. The results of this study that group guidance services with short film media methods can improve student discipline and there is a significant difference between the experimental class and the control class.